Prosedur Pelayanan Tamu di Food & Beverage Romeos Bar & Grillery - Putra, Made Heryk Kartika; Amir, Firlie Lanovia; idhyadanta, I Gede Dirga Surya Ary W (Penerbit Goodwood, 2024)
Purpose: This articel will analyze the implementation of Guest Service Procedures at Romeos Bar & Grillery in order to analyze how the implementation of standard service procedures at Romeos Bar & Grillery as well as the efforts made by the management to improve guest service at Romeos Bar & Grillery. Research methodology: This qualitative research gathered data through interviews and observations, providing a clear picture of service procedure implementation at the restaurant. Data analysis followed three steps: data reduction, data display, and conclusion drawing with verification.Results: From this study it was found that the guest service process at Romeos Bar & Grillery already has an appropriate standard where the operational standards of guest services here are developed from the sequence of service that has been applied internationally, and from the observation process carried out in the field it was found that the implementation of the SOP has been going well, but there are several steps that have not been carried out optimally.Conclusions: The implementation of standard service procedures at Romeos Bar & Grillery aims to ensure smooth operations and provide the best service for guests. To support the service, complete equipment is needed and improving the quality of human resources through training, awards, and strengthening teamwork. Improving time discipline and service efficiency are the main factors that need to be improved in order to improve the overall quality of service.Limitations: This study has limitations in the scope of observations which only focus on service procedures at Romeos Bar & Grillery, so it does not cover other aspects such as in-depth customer satisfaction or comparisons with similar restaurants.Contribution: Then regarding the process carried out by management in improving the service of the staff at Romeos Bar & Grillery, namely the on-job training process, off-job training, and also by carrying out activities that have been proclaimed by the Romeos Bar & Grillery.Keywords: Food & beverage service, Guest service procedures, ServiceHow to Cite: Putra, M, H, K. Amir, F, L. Widhyadanta, I, G, D, S, A. (2024). Prosedur Pelayanan Tamu di Food & Beverage Romeos Bar & Grillery. Jurnal studi perhotelan dan pariwisata, 3(1), 11-19.